2017
DOI: 10.1177/1471301217700742
|View full text |Cite
|
Sign up to set email alerts
|

Dementia and Clinical Interaction in Frontline Radiography: Mapping the Practical Experiences of Junior Clinicians in the UK

Abstract: Usage of any items from the University of Cumbria's institutional repository 'Insight' must conform to the following fair usage guidelines.Any item and its associated metadata held in the University of Cumbria's institutional repository Insight (unless stated otherwise on the metadata record) may be copied, displayed or performed, and stored in line with the JISC fair dealing guidelines (available here) for educational and not-for-profit activities provided that• the authors, title and full bibliographic detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Given this input, all four finally revised the total analysis independently and then collectively, ensuring an extended process of triangular consensus validation. [20] Data emergent from the parents' interviews were subject to the same procedures and are integrated into the formal analysis when they illuminate key concerns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this input, all four finally revised the total analysis independently and then collectively, ensuring an extended process of triangular consensus validation. [20] Data emergent from the parents' interviews were subject to the same procedures and are integrated into the formal analysis when they illuminate key concerns.…”
Section: Discussionmentioning
confidence: 99%
“…[13,21] The above findings highlight how preparing children to handle prospectively difficult contexts requires carefully tailored, individually sensitive action by Significant Others. [22] At the very least, interactions in medical imaging departments are more restricted than in other areas of healthcare, [20] occur in highly unfamiliar circumstances for most patients and are likely to be brief and singular. [23] Thus, the findings (particularly in stages 2 and 3 of the posited model) draw attention to how well clinicians themselves did actually read contexts and help patients against all likely (theoretical) odds.…”
Section: Discussionmentioning
confidence: 99%
“…[14,17] This order of concern is further developed in recent qualitative research in general radiography, which indicates how clinicians in the modern UK National Health Service (hereafter NHS) workforce rarely feel that they have time to be sensitive to the intricate interpersonal needs of patients, especially those most vulnerable, even when they are demonstrably well aware of them. [18][19][20] As such, both the actual and perceived need to 'rush on' to the next patient in broader staff-pressurised clinical environments can leave the practitioner conscious that (a) they have learned little from each encounter, and (b) that they may have 'short-changed' the patient in terms of the care that could ideally have been provided. It is reported that the personal and professional confidence of junior radiographers, in particular, is recurrently damaged as a result.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that the personal and professional confidence of junior radiographers, in particular, is recurrently damaged as a result. [19] With respect to the pertinent issue of healthcare management, meanwhile, both shortage and 'flux' in team constitution have been shown to deleteriously impact upon an individual's capacity to plan effectively and promote intra-team communication/coordination, all of which have strong implications for their own sense of professional worth as a departmental leader. [10,21] Indeed, and as Henwood and colleagues extensively demonstrate regarding leadership in the medical imaging domain, Consultant Radiographers typically rely upon a sense of consistency, and consistently reliable feedback, from other departmental staff in generating their own sense of self-efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…A UK study explored the practical experiences of early career diagnostic radiographers when managing patients with dementia, finding a lack of confidence and knowledge of dementia; it briefly discussed the roles of carers as being potentially positive or negative forces in the medical imaging situation. 10 Our research builds upon this with a holistic approach taking several viewpoints in exploring the experiences of people with dementia in the imaging department from the perspective of people with dementia, their carers, qualified radiographers and student radiographers…”
Section: Introductionmentioning
confidence: 99%